AFFILIATIVE HUMOR DALAM DIALOG FILM CEK TOKO SEBELAH KARYA ERNEST PRAKASA: KAJIAN PRAGMATIK - Nur Eka Zulfina Maulida; Sri Yanuarsih; I Wayan Letreng (Jurnal Bastra (Bahasa dan Sastra), 2025)
This article examines the characteristics of humor, specifically affiliative humor, found in the dialogue of the film Cek Toko Sebelah directed by Ernest Prakasa. The study employs a pragmatic approach based on Rod A. Martin’s (2021) theory, which defines affiliative humor as a type of humor intended to strengthen social bonds through light, non-offensive jokes. The findings reveal that affiliative humor appears in various interactions between characters through spontaneous conversations, everyday jokes, and witty responses to social situations. This type of humor functions not only as an element of entertainment but also as a communicative tool to foster closeness and comfort in social interaction. These findings emphasize that humor in film is not merely a form of entertainment, but also carries profound pragmatic functions. In the context of Indonesian culture, affiliative humor serves as a communicative bridge that reflects values of togetherness, solidarity, and emotional intimacy. Therefore, the analysis of this humor style is not only relevant to linguistic and pragmatic studies, but also essential in understanding social representations in popular media.